Question #6e509

2 Answers
Dec 24, 2016

google

To solve this problem using the knowledge of physics we assume that

  1. the bungee rope behaves as an ideal spring and Hook;s law is obeyed here.

  2. jumper just steps of bridge and falls straight downward.

  3. If the height of the jumper is neglected comparing with the length of the rope, the position of the jumper may be considered as a point.

  4. The loss in gravitational potential energy of the jumper provides the gain in potential energy of the stretched rope at the first lowest position of the jumper, ignoring dissipation of energy during elongation of rope.

Now if the elongation of rope be xx m for first downward trip then gain in PE of the rope will be
E_"rope"=1/2xxkx^2Erope=12×kx2

where

k->"force constant of the rope "=160Nm^(-1)kforce constant of the rope =160Nm1

Again the loss PE of jumper

E_"jumper"=mxxgxxhEjumper=m×g×h

where

m->"mass of the jumper"=61kgmmass of the jumper=61kg

g->"acceleration due to gravity"=10ms^-2gacceleration due to gravity=10ms2

h-> "fall of jumper" hfall of jumper

Here

h="length of relaxed rope" + "elongation of rope"=(20+x)mh=length of relaxed rope+elongation of rope=(20+x)m

So by conservation of energy

1/2xxkx^2=mxxgxxh12×kx2=m×g×h

=>1/2xx160x^2=61xx10xx(20+x)12×160x2=61×10×(20+x)

=>8x^2=61xx(20+x)8x2=61×(20+x)

=>8x^2-61x-1220=08x261x1220=0

=>x=1/16(61+sqrt(61^2+4xx8xx1220))~~16.73mx=116(61+612+4×8×1220)16.73m

The jumper jumps from 44m above the water level of the river . If we add the length (20m) of the relaxed rope with the elongation the total elongated length becomes 16.73+20=36.73m16.73+20=36.73m. This length being less than 44m, the jumper will not hit water..

At this stage the upward force on jumper due to elastic property of the rope Fuarr=kx=160xx16.73NF=kx=160×16.73N
and downward gravitational pull Fdarr=61xx10NF=61×10N
So net upward pull on the jumper
F_"net"uarr=Fuarr-Fdarr=160xx16.73N-61xx10N=2066.8NFnet=FF=160×16.73N61×10N=2066.8N

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
Let at the final position when oscillation stops the net elongation be yy m

At this stage the gravitational pull is the cause of stretching and by Hook's law we can write

kxxy=mgk×y=mg

=>y=(mg)/k=(61xx10)/160~~3.81my=mgk=61×101603.81m
Adding the length of the relaxed rope with it the lowest final position of the jumper will be 20+3.81)=23.81m20+3.81)=23.81m .

At this position the net force on the jumper will be Zero as he is at rest.

Dec 25, 2016

Alternate solution based on solution already posted by @dk_ch.

Explanation:

Following assumptions are made

  1. The bungee rope behaves as an ideal spring and obeys Hook's law.

  2. Jumper just steps off bridge and falls straight downward as shown below. The center of gravity in this position is almost at the level of platform where the jumper stands.
    ![http://www.ukbungee.co.uk](https://useruploads.socratic.org/ay43gASdRxquYDQPNLR9_jumptype_24_0_large.jpg)

  3. The other end of rope is tied at the center of gravity of the jumper. The picture of jumper at the time of reaching the lowest point is as shown below. As such the effective height of platform is taken as if the thickness of jumper is neglected as compared to the length of the rope.
    ![dangerous-business.com](useruploads.socratic.org)

The loss in gravitational potential energy of the jumper gets converted into kinetic energy of the jumper till relaxed length of rope is reached. Thereafter further loss of potential energy and kinetic energy is used to stretch the rope.

Taking downward direction as positive xx-axis and origin at the point where rope has no slack.

Potential energy stored in the stretched rope

PE_"rope"=1/2kx^2PErope=12kx2
where kk is spring constant of the rope =160Nm^(-1)=160Nm1
xx is elongation of the rope.

Also the loss of PE of jumper at the lowest point

PE_"jumper"=mghPEjumper=mgh
where mm is mass of the jumper.
gg acceleration due to gravity =9.81ms^-2=9.81ms2
hh is maximum fall of jumper="length of relaxed rope"+x_max

:. h=(20+x_max)m
By conservation of energy we get
1/2kx_max^2=mg(20+x_max)

Inserting given values we get
1/2 xx160x_max^2=61xx9.81xx(20+x_max)
=>80x_max^2=11968.2+598.41x_max
=>80x_max^2-598.41x_max-11968.2

Plotting this equation using the graphic tool and taking only the positive root as length can not be negative we get

my comp

=>x_max=16.53m

It is given that the jumper jumps from bridge 44m above the river. We see that lowest point is at a distance of h=20+16.53=36.53m from the bridge. This length is less than 44m. Therefore, the jumper will not get wet.

At this point only two force are acting on the jumper.
A. the upward force on jumper which can be found using Spring equation for force

F=-kx
F=-160xx16.53N,
-ve sign shows that force is in the upward direction.

B. Downward force as weight =mg=61xx9.81N

Net force on the jumper is sum of both forces =-160xx16.53+61xx9.81
=-2046.4N, rounded to one decimal place.